2006
DOI: 10.1007/s10554-006-9103-x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired coronary flow velocity reserve and aortic distensibility in patients with untreated hypercholesterolemia—an echocardiographic study

Abstract: In conclusion it may be stated that CFR and aortic distensibility indices can be evaluated simultaneously by stress TEE in HC patients. CFR and aortic distensibility were impaired in HC patients as compared to NC subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Nemes et al (46) described reduced CFR and increased indices of aortic stiffness [E(p) and E(s)] in patients with LAD coronary artery disease as compared with patients with normal epicardial coronary arteries. In addition to these findings in patients with coronary artery disease, Nemes et al demonstrated significant correlations between CFR and aortic stiffness in patients without coronary artery disease, but with hypertension, aortic valve stenosis, type-2 diabetes and hypercholesterolemia (16)(17)(18)(19). However, presence of an association between aortic stiffness and impaired CFR in MetS has never been evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nemes et al (46) described reduced CFR and increased indices of aortic stiffness [E(p) and E(s)] in patients with LAD coronary artery disease as compared with patients with normal epicardial coronary arteries. In addition to these findings in patients with coronary artery disease, Nemes et al demonstrated significant correlations between CFR and aortic stiffness in patients without coronary artery disease, but with hypertension, aortic valve stenosis, type-2 diabetes and hypercholesterolemia (16)(17)(18)(19). However, presence of an association between aortic stiffness and impaired CFR in MetS has never been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…This together with the decreased diastolic transmyocardial pressure gradient interacts with coronary flow and flow reserve (11). Significant correlations between coronary flow reserve and aortic stiffness parameters have been demonstrated in different populations such as hypertension, aortic valve stenosis, and hypercholesterolemia (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…1 Systolic and diastolic ascending aortic diameters (SD and DD, respectively) can be recorded by M-mode echocardiography at a level of 3 cm above the aortic valve from parasternal long-axis view. The SD and DD were measured at the maximum anterior motion of the aorta and at the peak of QRS complex on the simultaneously recorded ECG, respectively variety of diseases [10][11][12][13]. There are numerous techniques for assessing the early stages of vascular disease and stiffness including pulse wave analysis or direct measurements.…”
Section: Discussionmentioning
confidence: 99%
“…type-2 diabetes, 37 and hypercholesterolemia, 38 with significant correlations between the parameters. These studies confirm the relationship between the parameters of aortic stiffness and CFR.…”
Section: Reviews Continuedmentioning
confidence: 92%